Sodium, magnesium and zinc complexes of mono(phenolate) heteroscorpionate ligands. - Schofield, A; Barros, M; Cushion, MG; Schwarz, A; Mountford, P (2009)
The reaction of bis(3,5-dimethylpyrazolyl)methylphenol N(2)O(Ar)H (1) with NaH in THF formed dimeric [Na(kappa(2)-N(2)O(Ar))(THF)](2) (2), which contains a kappa(2)(N,O)-bound bidentate N(2)O(Ar) ligand. The reaction of 1 with Mg(n)Bu(2) gave the four-coordinate monomeric butyl compound Mg(N(2)O(Ar))(n)Bu (3), whereas with (n)BuMgCl, a mixture of products was formed, including the six-coordinate homoleptic species Mg(N(2)O(Ar))(2) (4). The reaction of [Na(kappa(2)-N(2)O(Ar))(THF)](2) with (n)BuMgCl also gave 3, as did the redistribution reaction of Mg(n)Bu(2) with 4. The reaction of 1 with Mg{N(SiRMe(2))(2)}(2) afforded the four-coordinate amide derivatives Mg(N(2)O(Ar)){N(SiRMe(2))(2)} (R = Me (6) or H (7)), together with 4. The reactions of 1 with ZnMe(2) or Zn{N(SiMe(3))(2)}(2) gave the monomeric compounds Zn(N(2)O(Ar))Me (8) and Zn(N(2)O(Ar)){N(SiMe(3))(2)} (9), respectively. The reaction 9 of with HCl formed Zn(N(2)O(Ar))Cl (11), and subsequent addition of LiN(SiHMe(2))(2) to 11 led to Zn(N(2)O(Ar)){N(SiHMe(2))(2)} (12). The reaction of 1 with either Zn{N(SiMe(3))(2)}(2) or 9 gave Zn(N(2)O(Ar))(2). The compounds 2, 3, 4, 6, 8, 9 and 11 were crystallographically characterized. Compound was very active for the ring-opening polymerization (ROP) of epsilon-caprolactone (epsilon-CL) but the process was very poorly controlled as judged by the M(n) and polydispersity index of the polymer. Compounds 3, 8, 9 and 12 gave poor conversions to poly(epsilon-CL) over extended periods. N(2)O(Ar)H = 2,4-di-tert-butyl-6-(bis(3,5-dimethylpyrazolyl)methyl)phenol.